Oxidation of W(110) studied by LEED and STM - SHVETS, IGOR; WU, HAN CHUN; BOZHKO, SERGEY; VADAPOO, SUNDAR; ULUCAN, SAVAS (My University, 2010)
The oxidation of W(110) was studied over a temperature a range of 1000 K to 1600 K at 1x10-6 Torr oxygen. The subsequent oxide structure was then characterized using Low Energy Electron Di_raction (LEED) and Scanning Tunneling Microscopy (STM). It was found that the resulting structure was remarkably similar to that of Mo(110)oxidized under similar conditions. Using the Mo(110) oxide structure as our basis, along with atomic resolution STM images, we have constructed a model for the surface oxide of W(110).
PUBLISHED
Keywords: Physics; Low Energy Electron Diffraction (LEED); Nanoscience & Materials